G372 Management of respiratory tract infections in down syndrome: A systematic review. (27th April 2016) - Manikam, L; Reed, K; Venekamp, R; Schilder, A; Littlejohns, P; Hayward, A; Lakhanpaul, M
Abstract : Aims: To systematically review the effectiveness of preventive and therapeutic interventions for RTIs in children and adults with DS. Methods: PubMed, Embase.com, CINAHL, the Cochrane Library and trial registries were searched for published and ongoing studies of respiratory tract diseases, cardiovascular diseases and obstructive sleep apnoea to provide a broad overview of the existing evidence base. These databases were searched for controlled trials, cohort studies and controlled before-after (CBA) studies and trial registries were searched for ongoing studies. Initially, all before mentioned study types were included to provide a broad overview of the existing evidence base. However, those with a critical risk of bias were excluded using the Cochrane risk of bias tool. Results: A total of 13, 575 records were identified from which five studies fulfilled the eligibility criteria and three fulfilled our criteria for data extraction. These three studies assessed the effectiveness of drugs for preventing RTIs in children with DS. One randomised controlled trial (RCT) of moderate risk of bias compared zinc therapy with placebo. Outcome data were only reported for 50 (78%) children who presented with "extreme" symptoms; no benefit of zinc therapy was found. One non-RCT with serious risk of bias included 26 children and compared pidotimod (a synthetic dipeptide with immunomodulatory properties) with no treatment; pidotimod was associated with fewer upper RTI recurrences compared with no treatment (1.43 vs. 3.82). A prospective cohort study with moderate risk of bias compared 532 palivizumab treated children under the age of 2 with 233 untreated children and found that children treated with palivizumab had fewer RSV-related hospitalisation (23 untreated, 8 treated) but the same number of overall RTI-related hospitalisations (73 untreated, 74 treated) in the first two years of life. Conclusions: The evidence base for the management of RTIs in people with DS is incomplete. Methodological rigorous studies are warranted to guide clinicians in how best to prevent and treat RTIs in people with DS.